2019
DOI: 10.4174/astr.2019.97.4.217
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility of da Vinci SP single-port robotic cholecystectomy: a case report

Abstract: The da Vinci surgical system released its new pure single-port platform, the da Vinci SP, offering improvements and refinements for established robotic single-site procedures. Herein, we present the first case of robotic single-site cholecystectomy using the da Vinci SP system (RSPC) demonstrating its safety and technical feasibility. A 59-year-old female with chronic calculus cholecystitis was admitted for elective RSPC. Docking time took 6 minutes. The patient underwent successful RSPC with a total operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
(10 reference statements)
0
23
0
Order By: Relevance
“…With the introduction of the new da Vinci SP surgical system, it is to the author's best knowledge that this is the first report on the early experiences on this new platform in the general surgical field, particularly in cholecystectomy. After experiencing a successful first case of RSPC [9], careful clinical application of the da Vinci SP robotic surgical system is increasing. According to the present results comparing RSPC and RSSC, it was noted that the overall postoperative complication rates, conversion rates, blood loss, and hospital stay were comparable between the 2 groups, suggesting that the da Vinci SP platform is feasible and equally as safe as the da Vinci Si and Xi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the introduction of the new da Vinci SP surgical system, it is to the author's best knowledge that this is the first report on the early experiences on this new platform in the general surgical field, particularly in cholecystectomy. After experiencing a successful first case of RSPC [9], careful clinical application of the da Vinci SP robotic surgical system is increasing. According to the present results comparing RSPC and RSSC, it was noted that the overall postoperative complication rates, conversion rates, blood loss, and hospital stay were comparable between the 2 groups, suggesting that the da Vinci SP platform is feasible and equally as safe as the da Vinci Si and Xi.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the present results showed that RSPC significantly reduced total operation time and its subsets; docking time, actual dissection time, and console time. As previously described [9], additional new features of the SP system include the fully-wristed endoscope, and a graphical user interface in the surgeon console and vision cart showing real-time position of instruments relative to each other. These differences may be attributed to several new features of the da Vinci SP system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After induction of general anesthesia, a hepatobiliary surgeon performed robot-assisted cholecystectomy using the da Vinci SP surgical system. 10 RNSM using the da Vinci SP surgical system was then performed as described in detail previously. 11 Briefly, RNSM was performed through a lateral incision 3.5 cm in size located on the midaxillary line at the level of the nipple.…”
Section: Methodsmentioning
confidence: 99%
“…So, there are some team using the Da Vinci Si Surgical System to operate cholecystectomy(41,42). A team has used Da Vinci SP for a 59 years old woman with chronic calculus cholecystitis to operate cholecystectomy in 89 minutes recently(43). Although the cholecystectomy…”
mentioning
confidence: 99%